United States : Financial System Stability Assessment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
Much of the Financial Sector Assessment Program (FSAP) work was conducted prior to the COVID-19 pandemic. The lockdown of the economy has led to a massive growth shock. Following the precipitous fall, risk asset prices have rebounded, and financial conditions eased. The vulnerability analysis has been updated and largely captures this shock. Recommendations on strengthening policy and institutional frameworks remain pertinent. The approach to financial regulation and supervision was risk-focused given the high degree of compliance against international standards assessed during the 2015 FSAP. .
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet